Distributed opportunistic scheduling algorithms for wireless communications. - Toan To (2012)
In this thesis, we propose a number of distributed schemes for wireless communications in the cross layer design context, considering an uplink random access network in which multiple users communicate with a common base station. In addition, we perform a comprehensive study on a splitting based multiuser selection algorithm which is simple, effective, and scales with the network size. First, we investigate a reservation-type protocol in a channel aware ALOHA system. Various Markovian models are used to describe the system and to capture the temporal correlation of the channel evolution. The average throughput of the system is obtained using the Markov Analysis technique and we show that the reservation protocol can achieve better performance than the original channel-aware ALOHA by reducing the collision probability. Second, for better resource utilization in the Opportunistic Multichannel ALOHA scheme, we propose a simple extension to the transmission policy that exploits the idle channels. Performance analysis shows that, theoretically, the maximum system throughput can be improved by up to 63% in the asymptotic case. Through numerical results, it can be seen that a significant gain is achieved even when the system consists of a small number of users. Third, we consider a splitting based multiuser selection algorithm in a probabilistic view. Asymptotic analysis leads to a functional equation, similar to that encountered in the analysis of the collision resolution algorithm. Subject to some conditions, the solution of the functional equation can be obtained, which provides the approximations for the expected number of slots and the expected number of transmissions required by the algorithm in a large system. These results shed light on open design problems in choosing parameters for the algorithm when considering the delay and the overhead jointly. A typical example is to optimize the parameters that minimize the weighted sum of these measures of interest.